The Influences of Family Supportive Supervisor Behaviors on the Relationships Among Work-Family Conflict, Stress, and Turnover Intention in Saudi Arabian Registered Nurses - (:unkn) unknown (My University, 2016)
Many countries around the world are struggling to maintain adequate number of nurses. Inadequate nurse staffing could compromise the quality of patient care. Among many factors that contribute to RN turnover, the influence of work–family conflict (WFC) has gained little attention. In Saudi Arabia, the turnover rate among Saudi nurses reached 50 % of the total employed nurses. Work-family conflict was found to be a reason that influence Saudi nurses to leave their workplace. In addition, WFC was found to be significantly association with increased turnover intention (TI) among employees. Furthermore, WFC has been linked to a number of negative consequences, including lower job satisfaction and organizational commitment, sleep insufficiency, insomnia symptoms, obesity, cardiovascular diseases, sleep insufficiency, and high cholesterol. In an effort to find strategies to manage the consequences of WFC, many behavioral, psychological, and career scholars have focused on the role of supervisor support. Family Supportive Supervisor Behaviors (FSSB) has been found to be a promising approach contributing to the reduction of TI in employees’ experiencing WFC. Despite the importance of work–family issues and the influence of FSSB, limited studies have been conducted among the nursing population and none were found that included a sample from Saudi Arabia. Therefore, the main Purpose of this study was to evaluate the influence of FSSB on the relationship among WFC, Stress, and TI in Saudi Arabian registered nurses. Method: A cross-sectional study. Sample: Convenience sampling; 113 Saudi female nurse. Result: Fifty percent of nurses intended to leave their workplace, 68 % of nurses reported having a conflict between work and family, and 44% reported high level of stress. A significant positive correlation was found between WFC and TI (r= .43, P
Keywords: Nursing Retention; Nursing Shortage; Supervisor Support; Turnover Intention